Clinical application of radiation dose reduction at abdominal CT. Issue 111 (February 2019) - Higaki, Toru; Nakamura, Yuko; Fukumoto, Wataru; Honda, Yukiko; Tatsugami, Fuminari; Awai, Kazuo
Highlights: Radiation exposure at CT examinations must be as low as reasonably achievable. Low X-ray tube voltage- and low X-ray tube current settings are used to reduce the radiation dose. Automatic exposure control optimizes the radiation dose, and iterative reconstruction reduces the images noise. To reduce the radiation dose at routine CT, the image noise can be reduced with techniques such as iterative reconstruction. Since many of advanced imaging involve higher radiation exposure, radiation reduction techniques must be applied. Abstract: Report VII of the Board on Radiation Effects Research (BRER), in which the linear no-threshold hypothesis was applied, estimates the lifetime carcinogenesis risk from computed tomography (CT) as 0.34 to 1.30%. Other studies provided evidence for breaks in double-stranded lymphocyte DNA in human blood during CT examinations. Although it cannot be claimed that such DNA damage is a direct cause of carcinogenesis, it is important to reduce the radiation exposure of patients subjected to CT studies. Here we focus on techniques and clinical applications of abdominal reduced-dose CT. With automatic exposure control (AEC), the X-ray tube current can be optimized and the noise level maintained uniformly, regardless of the target size. Iterative reconstruction can reduce the image noise on scans acquired at reduced radiation doses. Use of these techniques helped to reduce radiation exposure at routine examinations by about 20–40%. We also discuss advanced imaging methods such as dynamic perfusion CT.